Análisis de la imposición del impuesto al valor agregado a los servicios digitales en el Ecuador - Cashug Carrillo, Christhian Mauricio (2022)
The imposition of the Value Added Tax on digital services in Ecuador, which was carried out since December 2019, was carried out in order to strengthen the economy through tax reforms, based on the principles of progressivity, in addition to generating positive impacts on various sectors of the economy, since with the current pandemic, digital services become the solution to the distancing due to the new normality, these have already been growing since globalization, it was the service with the highest growth before and in the pandemic and therefore they have been always the highest income received by the State through the collection of value added tax. In this sense, the research is proposed with the objective of analyzing the behavior of VAT from the taxation of digital services in Ecuador. For this, it was necessary to develop the following mixed approach methodology, whose scope was bibliographic, documentary-descriptive, the technique used was the interview directed to two specialists in the subject of study. Regarding the results obtained, the important regulations that correctly regulate the collection of value added tax on the different digital services that are offered and operate in the country, by foreign companies, which due to omission or elusion did not declare and register, stand out. Taxes on their services, which evidenced an affectation to the income of the State, with this regulation it is sought to balance the deficit that exists in the country due to the increase in expenses.